PENERAPAN PEMBELAJARAN KOPERATIF DENGAN PENDEKATAN STRUKTURAL TPS DAN TSTS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X5 SMA NEGERI 1 TAMBANG - Azrina Purba (MES: Journal of Mathematics Education and Science, 2016)
AbstractThe research aimed to increase student’s mathematics learning of SMA Negeri 1 Tambang grade X5. This research was conducted on 36 students of grade X5 in SMA Negeri 1 Tambang through cooperative learning with approachment Think Pair Square (TPS) and Two Stay Two Stray (TSTS) technique. The material is about Linear and Quadratic Equation. This research was classroom action research. The subjects of this research was 36 students of grade X5 in SMAN 1 Tambang. The object of this research was to increase the student’s mathematics learning through Cooperative Learning with structural approachment TPS and TSTS technique for linear and quadratic equations. The instrument of this research was the student’s Mathematic result, observation, and interviews. The observations aimed to determine the researcher’s ability to manage the process of learning to determine the student’s prior knowledge was taken from student’s test before learning it was 15 (41.67%) of student reach KKM. After giving the cooperative learning with the structural TPS and TSTS technique, then giving the mathematics learning result (daily tests I). From the results of UH I data showed that as many as 20 (55.56%) students achieve KKM. Because of the results of students' mathematics learning as a whole has not been reached then resumed action on the second cycle. From the results of UH II data showed that 27 (75%) of students who reached the KKM. This means an increase in students' mathematics learning results from the first cycle to the second cycle. Keywords Mathematics Learning Result, Cooperative Learning, TPS, TSTS